Empowering wakaf and zakat in the provision of affordable housing through collaborative procurement - Abdul Rashid, Khairuddin; Mohd Fauzi, Puteri Nur Farah Naadia; Hasan, Sharina Farihah; Ayob, Mohd Fairullazi (EDP Sciences, 2019)
Wakaf and zakat are the two most important tools for assisting the poor and needy Muslims to have access to better living conditions. However, in the provision of affordable housing, efforts by the wakaf and zakat authorities are often hampered by constraints such as in the availability of funding and expertise. The purpose of this paper is to propose a conceptual model of collaborative procurement to empower wakaf and zakat in the provision of affordable housing for the poor and needy. It is contended that through collaborative procurement wakaf and zakat authorities would have better access to resources especially funding and technical expertise. The paper, an outcome of a robust desk research and discussions with experts, describes the concepts of wakaf, and zakat and their efforts to help the poor and needy including in the provision of affordable housing and collaborative procurement. In addition, a collaborative procurement model comprising of wakaf and zakat authorities and private property developer has been developed and herein proposed. The paper highlights issues and constraints, including those related to the Shariah. The research outcome, in terms of the proposed collaborative procurement model, contributes significantly towards empowering wakaf and zakat in the provision of affordable housing for the poor and needy.